Smart underground cylindrical parking system. - Yong, Tze Liang (2022)
This project is a robotic and IoT project made to help solve some problems related to parking. It will be an alternative choice for parking structures which can bring more benefits. As normal parking not only wastes space but also causes traffic congestion and is non-environmentally friendly. The article goes through more of the disadvantages of parking lots, and also going through some of the inventions that have been made. This project aims to use automation to solve these problems, at the same time bringing automation to the mainstream. We will be making a small-scaled prototype for demonstration purposes. From the design, RPi is chosen to be the brain of the system as it has several GPIO pins for the signals to control the components, it also is able to connect to a screen through HDMI port and is able to send signals to other systems. The motors used are stepper motors as it has high precision, which the system needs in order to not damage anything. The system will be using Geany as the programming software, and Python will be used as the programming language. The system will be able to retrieve data from the file, get input from user, compare data, save data, and control the other components. By receiving input from the user on whether to store or to retrieve, the system will do the respective processes before passing the data to the motor control process, which will calculate the angle and level for the motors in order to get to the specified slot. The entire structure will be made out of wood, use around 5 motors and RPi to control it. The process will be a loop, waiting for users to use the system while checking and updating the status when the system is used. The challenges face by this project will be the cost, tm and work that will have to be put in to actually implement in the real world. But in the end, there are still many improvements that can still be made to the system, which already makes it stand out to those systems that cannot.